MOTIVASI SISWA TERHADAP PEMBELAJARAN PENJASORKES DI SEKOLAH DASAR NEGERI 4 BENGKALIS - Hartati, Sri; Ramadi, Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract, This study aims to reveal the motivation of students towards learning penjasorkes at State Elementary School 4 Bengkalis. Motivation is one of the psychological aspect that encourages a person to an action ability to achieve the desired objectives. From the observation that the author did in elementary school physical education learning turns 4 Bengkalis not run well, it is proved by the results obtained student learning is still not as expected, the quantity of students that scored less still quite large. This type of research is descriptive. The population of 120 people, while a sample of 36 people. Types and sources of data are primary data and secondary data. Data analysis was performed by using a descriptive analysis analysis. Results of the study found that the highest indicators contained in item No. 7 questions proved respondents who answered yes were 30 people, meaning 83.3% meyatakan that often read-read books related to sports penjasorkes. And the question item No. 15 proved to respondents who answered yes were 38 people, meaning that 83.3% meyatakan very happy to see the game penjasorkes conducted in schoolsKeywords : Motivation